Deadlock in Georgia: Political crisis and regional changes need an EU response - Franziska Smolnik; Mikheil Sarjveladze; Giorgi Tadumadze (Stiftung Wissenschaft und Politik (SWP), 2021)
Since the parliamentary elections in October 2020, Georgia's government and opposition have found themselves in a political deadlock. This is evidenced above all by the fact that the majority of elected opposition parties have boycotted entering parliament. The country is not only facing domestic political challenges. The war over Nagorno-Karabakh has also changed the regional constellation. While Russia and Turkey have positioned themselves as influential actors in the region, the EU has been barely visible. For Georgia, which is the only country in the South Caucasus to have clear EU and NATO ambitions, this change is a potential threat to its pro-Western course. Tbilisi continues to have high expectations of the EU, which claims to be a geopolitical actor. Both the new regional context and the Georgian domestic political crisis should be an inducement for the EU to engage more with its eastern neighbourhood, and especially to give new impetus to its relations with Euro-Atlantic orientated Georgia.
Keywords: 320